2015
DOI: 10.4236/health.2015.712186
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Diabetes Oral Health Assessment Tool © for Nurses

Abstract: Although some studies have suggested a bidirectional relationship between diabetes and periodontal disease, there were no appropriate tools for nurses to evaluate oral status and oral health behaviors in patients with diabetes. Therefore, the Diabetes Oral Health Assessment Tool (DiO-HAT©) was developed with items contributed by health care professionals (diabetologists, periodontal specialists, a preventive dentist, a Certified Nurse in Diabetes Nursing, a national registered dietitian, registered nurses, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…In terms of internal consistency reliability, the reported ordinal Cronbach's alpha and Mcdonald's Omega coe cient were good (α = 0.82; ω = 0.87) for the entire one-dimension instrument, similar results than obtained by Kuwamura et al (40) but differing from the values obtained by Mello et al ( 26), who evaluated the internal consistency of the instrument applied by a group of nurses and dentists to 50 older people, obtaining alpha values considered to be low. In this respect, the following should be considered:…”
Section: Discussionsupporting
confidence: 82%
“…In terms of internal consistency reliability, the reported ordinal Cronbach's alpha and Mcdonald's Omega coe cient were good (α = 0.82; ω = 0.87) for the entire one-dimension instrument, similar results than obtained by Kuwamura et al (40) but differing from the values obtained by Mello et al ( 26), who evaluated the internal consistency of the instrument applied by a group of nurses and dentists to 50 older people, obtaining alpha values considered to be low. In this respect, the following should be considered:…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, the results obtained in the present research are sufficient to consider that the OHAT has structural validity. In terms of internal consistency reliability, the reported ordinal Cronbach's alpha and Mcdonald's Omega coefficient were good (α = 0.82; ω = 0.87) for the entire onedimension instrument, similar results than obtained by Kuwamura et al [41] but differing from the values obtained by Mello et al [26], who evaluated the internal consistency of the instrument applied by a group of nurses and dentists to 50 older people, obtaining alpha values considered to be low. In this respect, the following should be considered: first of all, it is important to note the definition of this measure, which is frequently considered to refer to the degree in which all elements of a test or instrument measure the same attribute or dimension [42].…”
Section: Discussionsupporting
confidence: 81%
“…As for oral care, nurses should discuss how they can help patients avoid getting worse and what they can do to improve patients' oral self-management. In a previous study (4,5), several nurses reported that they wished to conduct quick oral assessments because in real clinical settings they have to educate patients about several other aspects of the disease. Not surprisingly, the present study found significant relationships between the items of C-DiOHAT© ("use of supplementary tools") and the dentist's examination ("number of present teeth by sex and age" and "dentist's recommendation of dental examination").…”
Section: Discussionmentioning
confidence: 99%